Comparative study of pure RCC and graded RCC cattle through software based recording system in different regions of Bangladesh - Miah, Manik; Shejuty, Shahanaj Ferdousi; Kabir, Md Ahsanul; Hossain, SM Jahangir; Das, Dipa; Azmol, Syed Ali; Rahaman, Atikur; Amin, Md Ruhul (Asian-Australasian Journal of Bioscience and Biotechnology, 2023)
Recording systems are important to maintain data properly with a view to justifying the merits of productive and reproductive parameter as well as pedigree evaluation, towards any decision making pathway. Considering this, the current research was conducted to assess the computer and mobile software based animal recording system, which have important effect on production and reproduction on Red Chittagong cattle and their graded cattle. For this reason, this survey was conducted at well-developed pre-tested questionnaire through mobile application software under thirteen study areas. The study areas were selected based on the density of Red Chittagong Cattle population in those areas. After data collectionollected data were analyzed using SPSS 22.0 software and mean comparisons were estimated by LSD and Duncan method. Numbering (highest-11.32% at Godagari, lowest at Naikhongchari-4.25%), Artificial Insemination (highest 20% at Godagari and lowest at Naikhongchari-1%), service per conception rate (highest at Sylhet-1.37 and lowest at Swandip-1.14), calving rate (highest 12.34% at Anowara and lowest 4.20% at Keshobpur) and birth weight (highest 16.50±0.57 kg at Hathazari and lowest 12.79±0.49 kg at Godagari) were different in each regions. Lactation length, milk yield, and growth rate of two category cattle were found statistically significant (P<0.05) between two groups of cattle. These three productive parameters were higher for Red Chittagong Cattle (230±5.16 days, 3.10±0.13 L/day, 0.197 kg/day) respectively. The software based recording system helps to get proper data which will help for selection of superior sires and dams with high genetic merit as well as data can be restored anytime from this software based recording system. Asian Australas. J. Biosci. Biotechnol. 2023, 8(3), 70-77